2021
DOI: 10.1039/d0cp05555g
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical study on the impact of a nitrate group on the chemistry of alkoxy radicals

Abstract: The chemistry of nitrated alkoxy radicals, and its impact on RO2 measurements using the laser induced fluorescence (LIF) technique, is examined by a combined theoretical and experimental study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 100 publications
0
45
0
Order By: Relevance
“…H-Migration of an aliphatic or an a-ONO 2 -H-atom across the epoxide functionality is an order of magnitude faster than the predictions by the SAR by Vereecken and Nozière for corresponding H-migrations in non-cyclic RO 2 radicals. This contrasts with the results for epoxidized alkoxy radicals by Novelli et al, 49 who found little Table 5 Theoretical rate predictions for ring opening in nitrate-epoxy-alkyl radicals derived from isoprene + NO 3 , at the CCSD(T)/aug-cc-pVTZ//M06-2X/aug-cc-pVTZ with MC-TST level of theory. Indicated are the ZPE-corrected barrier height (E b , kcal mol À1 ), the 298 K rate coefficient (k(298 K), s À1 ), and the parameters for a Kooij expression k(T) = A  (T/K) n  exp(ÀE a /T) (A in s À1 , E a in K).…”
Section: Epoxy-alkyl Radicals: Ring Breaking Versus O 2 Additionmentioning
confidence: 70%
See 4 more Smart Citations
“…H-Migration of an aliphatic or an a-ONO 2 -H-atom across the epoxide functionality is an order of magnitude faster than the predictions by the SAR by Vereecken and Nozière for corresponding H-migrations in non-cyclic RO 2 radicals. This contrasts with the results for epoxidized alkoxy radicals by Novelli et al, 49 who found little Table 5 Theoretical rate predictions for ring opening in nitrate-epoxy-alkyl radicals derived from isoprene + NO 3 , at the CCSD(T)/aug-cc-pVTZ//M06-2X/aug-cc-pVTZ with MC-TST level of theory. Indicated are the ZPE-corrected barrier height (E b , kcal mol À1 ), the 298 K rate coefficient (k(298 K), s À1 ), and the parameters for a Kooij expression k(T) = A  (T/K) n  exp(ÀE a /T) (A in s À1 , E a in K).…”
Section: Epoxy-alkyl Radicals: Ring Breaking Versus O 2 Additionmentioning
confidence: 70%
“…Their fate as governed by the competition between unimolecular and bimolecular reactions is important not only for the atmospheric chemistry of isoprene, but also plays a critical role in the experimental detection of the nitrate-RO 2 radicals by a ROxLIF instrument. For the latter, we extend the recent work by Novelli et al 49 on nitrate-substituted alkoxy radicals (called nitrate-RO hereafter) to the nitrate-RO derived from isoprene. The chemistry of these unsaturated alkoxy radicals can proceed by reversible epoxidation and subsequent O 2 capture, which affects both the detection of RO 2 in the ROxLIF instrument, and the yield of MVK and MACR in the SAPHIR chamber and the atmosphere.…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations